Traces of Islamic Education Reform: The Role of Jami'at Khair and Al Irsyad in Building Public Awareness - Endah Setyadinanti; Lulu Afindasari; Naila Fitriyani Ridwan; Sutrimo Purnomo (Aimmah: Social Sciences Journal, 2026)
This study aims to examine the history, figures, and roles of the educational institutions Jami’at Khair and Al-Irsyad in the development of Islamic education in Indonesia. This research uses a library research method by reviewing various written sources such as books, scientific journals, and other references relevant to the topic. The results of the study show that Jami’at Khair was one of the Islamic organizations that played an important role in the reform of Islamic education in the early 20th century. This organization implemented a more modern education system by incorporating general subjects into the curriculum and applying a classical learning system. In its development, differences of opinion emerged between Ahmad Surkati and several leaders of Jami’at Khair regarding the concept of equality among Muslims. These differences later led to the establishment of a new organization, Al-Irsyad. Al-Irsyad then developed as an organization engaged in education, da'wah, and social activities by emphasizing the purification of Islamic teachings and the importance of returning to the Qur’an and Sunnah. Therefore, Jami’at Khair and Al-Irsyad have played an important role in the history of Islamic educational reform in Indonesia, particularly in developing the education system, Islamic thought, and improving the quality of Muslim society.